Suitability and availability analysis of tropical forest wood species for ethanol production: a case study in East Kalimantan - RUDIANTO AMIRTA; AHMAD MUKHDLOR; DEWI MUJIASIH; ELIS SEPTIA; SUPRIADI SUPRIADI; DWI SUSANTO (Society for Indonesian Biodiversity, 2016)
Amirta R, Mukhdlor A, Mujiasih D, Septia E, Supriadi, Susanto D. 2016. Suitability and availability analysis of tropical forest wood species for ethanol production: a case study in East Kalimantan. Biodiversitas 17: 544-552. Fifteen species of woody biomass from tropical forest of East Kalimantan, Indonesia and identified as Acacia mangium, Aleurites moluccana, Alstonia scholaris, Anthocephalus cadamba, Artocarpus altilis, Artocarpus elasticus, Cananga odorata, Gmelina arborea, Lagerstroemia speciosa, Leucaena leucocephala, Macaranga gigantea, Macaranga tanarius, Paraserianthes falcataria, Shorea leprosula and Swietenia macrophylla were characterized and studied to find out and discover their potential utilization as suitable feedstocks for biofuel (ethanol) production. Characterization was done by evaluation of lignin, holocellulose and cellulose contents of woody biomass including the yield of reducing sugar (saccharification) after pretreated with alkaline (NaOH) at moderate temperature. Among 15 species of tropical forest wood biomass evaluated, our findings showed that M. gigantea was gave the highest yield of saccharified sugar (42.22%, weight of original wood dry basis) and also yield of theoretical ethanol (Â± 273 L/ton). We also found growth of M. giganteawas very fast to produce approximately 26,119 kg ha-1 dry biomass within 3 years. In general, the tropical wood biomass such as M. gigantea, A. moluccana, G. arborea, A. cadamba, and P. falcataria are suitable and potentially to be used as feedstocks for ethanol production due to their fast growing ability, availability and attractive chemical composition to produce high saccharified sugar and yield of ethanol.